Faktor neurotrofik yang diturunkan dari otak dalam darah meningkat sementara setelah sesi tunggal latihan intensitas sedang pada wanita gemuk - Raharjo, Slamet; Harisman, Ahmad Syahru Mubarok; Andiana, Olivia; Pamungkas, Yualita Putri (Universitas Nusantara PGRI Kediri, 2021)
This study aimed to analyze the increase in serum BDNF levels after moderate-intensity exercise in obese females. This study used the True-Experimental method with the Randomized Control Group Pre-test-Post-test design. A total of 14 obese female adolescents aged 19-24 years participated in this study and were divided into two groups, i.e., the control group (CG, n=7) and the moderate-intensity exercise group (MIEG, n=7). The exercise was performed with an intensity of 64 – 76 HRmax for 40 minutes using a Richter Treadmill (4.0 HP DC). Moderate-intensity exercise was carried out in one intervention. Blood sampling was carried out before and after moderate-intensity exercise on the cubital vein as much as 3 ml. Examination of serum BDNF levels using the ELISA method. The results of statistical analysis show that the mean pre-test serum BDNF levels were CG (258.66±27.11 pg/mL), MIEG (252.48±23.17 pg/mL), and (p=0.865). The mean post-test serum BDNF levels were CG (236.22±20.83 pg/mL), MIEG (497.73±59.55 pg/mL), and (p=0.001). The mean delta of serum BDNF levels on CG (-22.43±26.04), MIEG (245.25±61.57 pg/mL), and (p=0.002). Based on the study results, it is concluded that a single session of moderate-intensity exercise in the morning increases serum BDNF levels in obese females.